2018
DOI: 10.1016/j.celrep.2018.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Knockout of Two Presumed Forelimb Tbx5 Enhancers Reveals They Are Nonessential for Limb Development

Abstract: SUMMARYA standard approach in the identification of transcriptional enhancers is the use of transgenic animals carrying DNA elements joined to reporter genes inserted randomly in the genome. We examined elements near Tbx5, a gene required for forelimb development in humans and other vertebrates. Previous transgenic studies reported a mammalian Tbx5 fore-limb enhancer located in intron 2 containing a putative retinoic acid response element and a zebrafish tbx5a forelimb (pectoral fin) enhancer located downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…Comparison of mouse Aldh1a2 and Rdh10 RA synthesis mutants (Zhao et al, 2009;Cunningham et al, 2013) revealed that RA repression of both caudal and cardiac Fgf8 domains is needed for Tbx5 activationthe earliest known marker in the forelimb bud. Other studies propose that RA might directly activate Tbx5 via a RARE located in intron 2 (Nishimoto et al, 2015), however subsequent enhancer knockout experiments showed that this RARE is not required (Cunningham et al, 2018). Thus, the most parsimonious model is that RA permits forelimb Tbx5 expression by repressing Fgf8, which allows another factor to activate Tbx5.…”
Section: Ra Is Required For Forelimb Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of mouse Aldh1a2 and Rdh10 RA synthesis mutants (Zhao et al, 2009;Cunningham et al, 2013) revealed that RA repression of both caudal and cardiac Fgf8 domains is needed for Tbx5 activationthe earliest known marker in the forelimb bud. Other studies propose that RA might directly activate Tbx5 via a RARE located in intron 2 (Nishimoto et al, 2015), however subsequent enhancer knockout experiments showed that this RARE is not required (Cunningham et al, 2018). Thus, the most parsimonious model is that RA permits forelimb Tbx5 expression by repressing Fgf8, which allows another factor to activate Tbx5.…”
Section: Ra Is Required For Forelimb Initiationmentioning
confidence: 99%
“…RAR chromatin immunoprecipitation studies have reported 13,000-15,000 potential RAREs in the mouse genome (Moutier et al, 2012). However, most of these RAREs might not be required for development, owing to weak affinity to RARs or having locations within the genome that are not normally able to control nearby genes (Cunningham et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In one additional case, a RARE described within intron 2 of Tbx5 that was suggested to be required for activation of Tbx5 in the forelimb field based on enhancer reporter transgene analysis 12 was found to be unnecessary for Tbx5 activation and forelimb budding when subjected to deletion analysis 13 . It is now clear that RAREs (and other DNA control elements) that exhibit appropriate tissue-specific expression in enhancer reporter transgene assays (where the element is inserted at a random location in the genome) are often not required in vivo 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study using CRISPR/Cas9 technology to delete the intron 2 sequence specifically indicates that regulatory elements within this region are not required to establish Tbx5 expression in the forelimb bud and that forelimbs can form normally in the absence of this element [39]. This study also used the same deletion strategy to test a conserved Tbx5 regulatory element uncovered by phylogenetic foot printing [40].…”
Section: Retinoic Acid Is Required For Limb Induction and Initiationmentioning
confidence: 99%